A systematic literature review of industry 4.0: bridging between the information asymmetry and corporate governance/ Mohd Hasimi Yaacob and Ng Suat Thing - Yaacob, Mohd Hasimi; Ng, Suat Thing (Faculty of Information Management, 2021)
With the growing literature on information asymmetry and industry 4.0 (IR4.0), a systematic review of the application of IR4 on mitigating information asymmetry is inevitable. Most of the existing literature focuses on management and computer science, and limited study links the analysis directly to the impact of technology on mitigating information asymmetry in corporate governance. Therefore, this study aims to fill in the literature gaps by refining and identify the linkage between adoption IR4.0 or enabling technologies of IR4.0 (Blockchain, Cyber-Physical System (CPS), Internet of Things (IoT), and Cloud Computing) related to mitigating information asymmetry. Firstly, the systematic review found 521 research articles from Scopus and Web of Science database and analysed nine articles based on inclusion and exclusion criteria. The review analysis found that blockchain technology plays a vital contribution in representing the enabling technologies of IR4.0. Most of the review analysis discussed blockchain technology on mitigating information asymmetry in corporate governance. Only one review article discussed widely with enabling technologies of IR4.0 on mitigating information asymmetry. However, the management field report was discussed too widely with theory and concepts related to computer science literature. Therefore, this study will focus on the discussion of blockchain technology on mitigating information asymmetry. The findings conclude that the enabling technologies of IR4.0 will mitigate information asymmetry in the corporate governance in the form of enabling open information transactions, decentralised governance, representing faithfulness of financial reporting, promote smart contracts, and enhance market competitiveness and social welfare. Finally, this study emphasised a framework based on the systematic literature review with suggested that IR4.0 will be a new mechanism to mitigate information asymmetry in the corporate governance, which will directly influence the intention of the corporate governance players to mitigate information asymmetry.